2016
DOI: 10.1108/ijge-10-2014-0034
|View full text |Cite
|
Sign up to set email alerts
|

Feminist perspectives on social entrepreneurship: critique and new directions

Abstract: Access to this document was granted through an Emerald subscription provided by emerald-srm:331053 [] For AuthorsIf you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 79 publications
(121 reference statements)
0
43
0
3
Order By: Relevance
“…For example, Muntean and Ozkazanc-Pan ( 2016 ) suggested that social enterprises can help foster reconciliation policies, such as flexible time or parental leave, which act as a motivating factor, encouraging women's career advancement.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Muntean and Ozkazanc-Pan ( 2016 ) suggested that social enterprises can help foster reconciliation policies, such as flexible time or parental leave, which act as a motivating factor, encouraging women's career advancement.…”
Section: Resultsmentioning
confidence: 99%
“…This is notable given that women are disproportionately engaged in nonprofit and social enterprises. Muntean and Ozkazanc‐Pan () point out that an over‐identification of women with social entrepreneurship poses the risk of reinforcing their role as “other” while suggesting that they are not capable of launching for‐profit growth‐oriented ventures. Thus, a singular policy focus on for‐profit ventures or on social entrepreneurship for women reaffirms the position of women entrepreneurs as “other” and assumes that other modalities of enterprise are neither valued nor growth‐oriented (Baker and Welter, ; Welter et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…We view gender as a social structure that influences values and action "indirectly by shaping actors' perceptions of their interests and directly by constraining choice" (Risman, 2004, p. 432). Popular descriptions of social entrepreneurs evoke gendered descriptions that blend stereotypically masculine (entrepreneur) and feminine (social) traits (Clark Muntean and Ozkazanc-Pan, 2016). Gender is therefore a contextual factor that affects values and action at the individual, organisational and institutional levels.…”
Section: Religious Faith Values and Social Entrepreneurshipmentioning
confidence: 99%